Usefulness of transcranial Doppler ultrasonography in the diagnosis of occlusive vascular lesions in the carotid territory - MAEDA, Hiroaki; ITOH, Taiji; MATSUMOTO, Masayasu; HANDA, Nobuo; OKU, Naohiko; HOUGAKU, Hidetaka; NISHIMURA, Tsunehiko; IIJI, Osamu; KAMADA, Takenobu; HASHIKAWA, Kazuo; MORIWAKI, Hiroshi; TSUKAMOTO, Yoshitane (Neurosonology, 1994)
The first pupose of this study was to assess the availability of transcranial Doppler ultrasonography (TCD) for detecting occlusive vascular lesions in the carotid territory. Secondly, we investigated the hypothesis that TCD reflects the state of cerebral perfusion, compared with single photon emision tomography (SPELT) . In 57 control subjects, the normal range was defined as a 95% confidence interval of flow velocity in the middle cerebral artery (MCA) (peak flow velocity; MCAPF, mean flow velocity; MCAMF) . We investigated the diagnostic accuracy for detecting occlusive vasclar lesions in 46 patients who had undergone both TCD and carotid angiography. Unilateral occlusion of the internal carotld artery (ICA) was shown in 15 patients (UIO), unilateral severe stenosis of ICA was seen in 9 (UIS), unilateral severe stenosis of MCA truncns was seen in 15 (UMS) and no abnormal findings in the major cerebral arteries in 7 (NF) . Side-to-side differences in the MCA territory of the cerebral blood flow was analyzed by SPECT in 27 patients (UIO; 9, UIS; 4, UMS; 15, NF; 7) . The normal ranges are as follows; 52<MCAPF<116cm/s, 30<MCAMF<73cm/s, FVR-peak<1.33 and FVR-mean< 1.37. By using these criteria, the diagnostic accuracy was 78% (36/46: UIO; 13/15, UIS; 5/9, UMS; 12/15, NF; 6/7) . A high rate of concordance for side-to-side differences between TCD and SPELT was found (25/27; 89%, UIO; 9/9, UIS; 3/4, UMS; 7/7, NF; 6/7) . In conclusion, TCD proved to be a quite useful method for diagnosing occlusive vascular lesions in the carotid territory. From the results of cross-comparison study of TCD and SPELT, TCD closely reflected the state of cerebral perfusion.